THE CONCEPT OF THE PROPHET IN BUILDING DOMESTIC HARMONY - Muhammad Fathur Rahcman Imanda; Winning Son Ashari (JURNAL HAKAM, 2025)
This study analyzes the Prophetic concept of building household harmony through family-related hadiths found in Sahih Bukhari and Sahih Muslim. The research is motivated by Indonesia’s high divorce rate in 2023, which reached 408,347 cases, with 251,828 due to disputes and conflicts indicating a gap between Islamic ideals and actual domestic practices. This study utilises a qualitative method with a library research approach, relying on primary data in the form of the Prophet's hadiths related to family life, as well as secondary data obtained from books, journals, and scientific articles.. The findings reveal that Prophet Muhammad shallallāhu ‘alaihi wa sallam practiced values such as active participation in household duties, praising his wife, bathing together, resting on his wife’s lap, prioritizing his wife, using affectionate nicknames, traveling together, and engaging in meaningful conversations. These practices significantly contributed to achieving a family life characterized by sakinah (tranquility), mawaddah (affection), and rahmah (compassion). Thus, the hadiths in Sahih Bukhari and Sahih Muslim offer authentic and applicable guidance for fostering harmonious Muslim families in the modern era.